Industrialización de granos andinos” cerveza artesanal de quinua “atiy” - Hidalgo Ortiz, Jessica Leonor (2016)
The quinoa beer “ATIY” obtained by a traditional method is a product, which represents a great opportunity for agroindustrial innovation, and improvement into Andean grains field because it offers a new alternative with quality to both producer and consumer. The objective of this research was: to yield a craft beer by the use of quinoa malted grain of a sweet variety (INIAP TUNKAHUAN) since its low saponin content. The technology of craft beer extraction was determined where the parameters that stand behind the product quality were controlled, and researchers stressed in malted conditions of quinoa grain; besides, a group of experts to evaluate the acceptability of the final product characteristics carried out a survey. A physicist, chemical, and microbiological characterization was made to guarantee the quality and safety to consumers. An analysis of prepared product was made. Finally, the technology was spread to get a development of food sovereignty. The beer obtained with quinoa malt had characteristics of high acceptability. The sweet variety of quinoa grain were used, which are giving them compliance with the INEN 1673 standard. The kept malted conditions were: eight hours of soaking and two days of germination with a limited amount of oxygen that stops the process. The utilized mill type was ground.